Hubungan mekanisme koping dengan kualitas hidup pasien gagal ginjal kronik yang sedang menjalani hemodialisis - Luftia, Ayu (Jurnal Health Society, 2025)
Background: Chronic renal failure is a kidney disorder characterised by structural abnormalities. One treatment that can be done is haemodialysis. The purpose of this study was to determine the relationship between coping mechanisms and quality of life of patients with chronic renal failure who were undergoing haemodialysis in the Hemodialysis Room of UOBK RSUD R. Syamsudin, SH. Sukabumi City. Method: This type of research is correlational with a cross sectional approach. The population was all chronic renal failure patients who were undergoing regular haemodialysis in the Hemodialysis room UOBK RSUD R. Syamsudin, SH. Kota Sukabumi with a sample of 113 people using total sampling. Data collection techniques using questionnaires. Data analysis techniques using descriptive analysis and chi squared test. Result: The results showed that most respondents had adaptive coping mechanisms, namely 61 people (54.0%) and had good quality of life, namely 63 people (55.8%). The chi-square test results show that there is a relationship between coping mechanisms and the quality of life of GGK patients who are undergoing haemodialysis. Conclusion: There is a relationship between coping mechanisms and quality of life of patients with GGK who are undergoing haemodialysis in the Hemodialysis Room of UOBK R. Syamsudin, SH. Sukabumi City.